Effect of exercise training on right ventricular remodelling induced by pulmonary arterial hypertension - Morais, Filipe Miguel Pinto (2019)
Pulmonary arterial hypertension (PAH) is a deadly disease characterized by progressive remodelling of the pulmonary arteries, causing a rise in pulmonary vascular resistance and overloading the right ventricle (RV). The RV response to the overload is the main prognostic determinant. Since exercise training provides several cardiovascular benefits in both physiological and pathological conditions, its use as a therapeutic tool for PAH has been hypothesised. In this work, we first performed a narrative review summarizing the current evidence about the mechanisms underlying the cardioprotective effects of exercise training in PAH (Chapter II). Our review suggests that exercise training prevents the remodelling of ECM (decrease fibrosis and modulation of MMPs/TIMPs), stimulate angiogenesis, reduce inflammation (decreased cell infiltration and levels of TNF-α and IL-6) and oxidative stress. Secondly, we extended the comprehension of the cardioprotective effects of exercise training in PAH by exploring the metabolic changes promoted by exercise. In order to do so, we used the monocrotaline animal model of PAH submitted to two weeks of treadmill exercise training (5 days/week, 60 min/day, 25 m/min). Our data shows that exercise training delays the progression of the disease, as trained rats had improved diastolic function (lower end-diastolic pressure and tau) despite the presence of cardiac overload (increased peak systolic pressure, end-diastolic pressure and arterial elastance). This improved hemodynamic response was paralleled by an increased uptake of glucose to cardiomyocytes through GLUT4 followed by its oxidation to lactate. Exercise did not revert the decrease of fatty acid oxidation related to PAH. This metabolic remodelling was associated to an increase of PGC1α and PPARγ protein expression. Overall, our work supports the recommendation of exercise training for the management of PAH.